The new Italian and Albanian archaeological project in Butrint (2015-2018) - Enrico Giorgi; Belisa Muka (Groma, 2018)
As it is well known to the scholars of ancient Albania, the history of Italian research in Northern Epirus is well established and began at least at the end of 1920s, with the Italian Archaeological Missions of Luigi Maria Ugolini, who worked in Phoinike first and then moved to Butrint. Thanks to this excavation, many of the monuments still visible in the current Butrint archaeological parc were brought to light.